Model of information systems success Delone and Mclean in using Pedulilindungi application in the tourism sector of Malang City - Syarif Hidayatullah; Stella Alvianna; Anisa Zuhria Sugeha; Widji Astuti (Universitas Merdeka Malang, 2022)
Currently all tourist attractions in the city of Malang have the PeduliLindungi application installed. The application is one of the requirements so that visitors can enter tourist attractions during PPKM. The PeduliLindungi application is also used as an anticipation of exposure to Covid-19 in the tourist environment. Moreover, epidemiology experts have also warned to be alert to the third wave of Covid-19, as a result, a fast application is needed to provide information about covid. The purpose of this study is to look at the use of the PeduliLindungi application system on the visitor side of the existing Desatinasi by looking at the quality of the system, the quality of information and the quality of service provided by the application, especially visitors to the tourism sector in Malang City. The population of this study is all people who have used services in all tourism sectors such as (tourist attractions, transportation, cafes, malls, hotels, and cinemas), the number of samples is 252 respondents with the sampling technique used is accidental sampling. The analysis used is descriptive, analysis of multiple linear regression, hypothesis testing (F test, t test) and coefficient of determination (R2) test. The results of the study 1) System quality, information quality and service quality have a positive effect on user satisfaction of the PeduliLindungi application. 2) The quality of the system has no direct effect on net benefits. 3) Information quality and service quality have a positive effect on the net benefits of using the PeduliLindungi application. 4) The quality of the system has a positive effect on net benefits through user satisfaction of the PeduliLindungi application. 5) Information quality and service quality have no effect on net benefits through user satisfaction of the PeduliLindungi application